Design and control of a droop-controlled microgrid - Li, Yaohua (Nanyang Technological University, 2021)
Droop control has been adopted in conventional power system widely. With high penetration of distributed generators(DGs) in modern power system especially in low voltage distribution system, it is necessary to explore different control schemes to improve the stability and reliability of microgrid. This dissertation investigated an advanced droop control method in microgrid and simulated a specific VSI-based microgrid with active load. Different controllers such as voltage controller, current controller and power controller were well-designed in small-signal state-space form in this dissertation. The designed microgrid along with the developed droop control schemes are simulated in Matlab/Simulink. Different control objectives such as output P&Q control, terminal voltage control and automatic power sharing control were achieved in this dissertation.